Stomatal closure is induced by hydraulic signals and maintained by ABA in drought-stressed grapevine - Tombesi, Sergio (Sci Rep, 2015)
Water saving under drought stress is assured by stomatal closure driven by active (ABA-mediated) and/or passive (hydraulic-mediated) mechanisms. There is currently no comprehensive model nor any general consensus about the actual contribution and relative importance of each of the above factors in modulating stomatal closure in planta. In the present study, we assessed the contribution of passive (hydraulic) vs active (ABA mediated) mechanisms of stomatal closure in V. vinifera plants facing drought stress. Leaf gas exchange decreased progressively to zero during drought, and embolism-induced loss of hydraulic conductance in petioles peaked to ~50% in correspondence with strong daily limitation of stomatal conductance. Foliar ABA significantly increased only after complete stomatal closure had already occurred. Rewatering plants after complete stomatal closure and after foliar ABA reached maximum values did not induced stomatal re-opening, despite embolism recovery and water potential rise. Our data suggest that in grapevine stomatal conductance is primarily regulated by passive hydraulic mechanisms. Foliar ABA apparently limits leaf gas exchange over long-term, also preventing recovery of stomatal aperture upon rewatering, suggesting the occurrence of a mechanism of long-term down-regulation of transpiration to favor embolism repair and preserve water under conditions of fluctuating water availability and repeated drought events.